PILOTING A RAPID ASSESSMENT TOOL IN CHILDREN'S ED. Issue 12 (18th November 2016) - Issa, S; Cole, R; Alcock, A; Sajjanhar, T; Selby, N
Abstract : Objectives & Background: The Children's Emergency Department at University Hospital Lewisham sees up to 130 attendances daily. This can result in delays to triage and sick children being missed. In our department, 50–84% of children are triaged within 15 minutes (monthly variation). Peak median time to triage is 41 mins and can depend on skill mix. Our objective was to create a safe Rapid Triage Tool to assess patients rapidly and identify the most unwell patients early. Recent RCEM work on Vital Signs in Children Clinical Audit 2015–16 indicated the need for improvement. Our project supports standards 1 and 3. It can also help to meet the KPI for initial assessment of ambulance patients and the RCEM pain targets. Methods: Rapid Assessment Tools were designed by extrapolating from the Manchester Triage System. One for trauma/injury and a second for medical illness figures 1 and 2. ▸ Pilot of 40 patients triaged- weekdays, evenings, weekends and night shifts ▸ Rapid Assessment was employed when the wait for triage was greater than 30 minutes and there were more than 3 patients waiting. It was done in one minute by a senior nurse with relevant training ▸ The nurse assesses the patient using the proforma, assigns a priority and indicates what actions are required ▸ Secondary nurse then acts on these and completes the triage- Figure 3. Results: 40 patients were assessed using the Rapid Assessment Tool. ▸ Qualitative correlation to the traditional triage was made and the patients were shown to be given the same priority ranking in all cases ▸ It takes less than a minute to perform the Rapid Assessment compared to 5–20 minutes for the traditional triage. ▸ Flow through the initial stages in the department was quicker ▸ There was better use of the nursing skill mix ▸ The sickest patients were identified faster ▸ Figure 4 Conclusion: This Rapid Triage Tool may be a safe tool to use in replacement of the traditional triage method. The perception from staff was that this felt safer and reduced the workload when there was large volume of patients. Further work ▸ Training is required to standardise the implementation of the Rapid Triage Tool ▸ A larger pilot will be conducted to make quantitative conclusions about the effects this has on overall triage time, time to treatment and the on meeting the RCEM Vital Signs and Pain Standards and the KPI ▸ This project has identified a number of areas for improvement such as an extra HCA at triage to facilitate the observations and providing all staff with mobile saturation probesFigure 1 Figure 2 Figure 3